Comparison of nitrogen-doped graphene and carbon nanotubes as supporting material for iron and cobalt nanoparticle electrocatalysts toward oxygen reduction reaction in alkaline media for fuel cell applications. (7th September 2016) - Ghanbarlou, Hosna; Rowshanzamir, Soosan; Parnian, Mohammad Javad; Mehri, Foad
Abstract: In this work the electrocatalytic performance of nitrogen-doped graphene (NG)-based non-precious metal (NPM) catalysts for oxygen reduction reaction (ORR) have been compared with their counterparts while supported on multiwalled carbon nanotubes (MWCNTs). Fe and Co nanoparticles were precipitated on NG (M/NG, M = Fe, Co) and for comparison on MWCNTs (M/MWCNT, M = Fe, Co) using a modified polyol method. The electrocatalytic properties of all catalysts towards oxygen reduction reaction in 0.1 M KOH solution were investigated. In comparison with M/MWCNTs, M/NG catalysts exhibited higher ORR activity, which indicates a better electrocatalytic performance of nitrogen-doped graphene compared to those which were supported by MWCNTs. Chronoamperometric results also demonstrated that the Co/NG catalyst was more stable for ORR in alkaline solution rather than Co/MWCNT and commercial Pt/C. Graphical abstract: Highlights: Nitrogen doped graphene (NG) was synthesized through solvothermal reaction and MWCNTs were functionalized to create active sites for metal nanoparticles deposition. Fe and Co nanoparticles were precipitated on synthesized NG and functionalized MWCNTs. The electrocatalytic performance of M/NG catalysts was higher than those of M/MWCNT. M/NG catalysts could potentially provide much higher durability than those of M/MWCNT.